Portraits of Chinese women in revolution - Smedley, Agnes (Light on China, 2004)
The China Society for People's Friendship Studies (PFS) in cooperation with the Foreign Languages Press (FLP) in Beijing has arranged for re-publication, in the series entitled Light on China, of some fifty books written in English between the 1860s and the founding years of the People's Republic, by journalistic and other sympathetic eyewitnesses of the revolutionary events described. Most of these books have long been out of print, but are now being brought back to life for the benefit of readers in China and abroad.